Analisis Psikometrika Properti dan Latent Sub Kelas dengan Mixture Rasch Model Pada Skala Organizational Commitment Questionnaire (OCQ) versi Indonesia - Widodo Setya Budi, Fransiscus; Kurniawan, Alexander Bhirowo Putra; Yudiarso, Ananta (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
This study evaluates the psychometric properties of the Indonesian version of the Organizational Commitment Questionnaire (OCQ) using the Rasch Model and Mixture Rasch Model. A quantitative approach was used to analyze data from 253 participants obtained through a survey using a convenience sampling technique. The points analyzed are related to validity, reliability, and unidimensionality and heterogeneity of response patterns. Results indicate that the affective, continuance, and normative subscales exhibit adequate evidence of unidimensionality, with raw variance explained ranging from 44% to 46%. Reliability testing revealed high item reliability (0.97–0.98) but moderate to low person reliability (0.58–0.66), suggesting limited sensitivity of the instrument to individual variations. Differential Item Functioning (DIF) analysis identified significant bias in several items of the affective and continuance subscales based on gender and education, while the normative subscale was neutral to these demographic variables. The Mixture Rasch Model analysis revealed heterogeneity in response patterns, with the two-class latent model showing lower AIC, BIC, and CAIC values compared to the one-class model, indicating a better fit. This study demonstrates that the Indonesian version of the OCQ can be utilized to measure organizational commitment but requires item adjustments to improve measurement sensitivity and fairness